Economic geography - Alexander, John W.; Gibson, Lay James (New Jersey : Prentice-Hall, 1979)
This book adopted a deliberate strategy. Geography, like most disciplines, is going through a transition period in which increasing attention is being given to quantification and the use of statistical methods of analysis.
Part One. Introduction -- Part Two. Subsistence economic activities -- Part Three. Commercial gathering of animals and plants -- Part Four. Commercial bioculture -- Part Five. Commercial mining -- Part Six. Commercial manufacturing -- Part Seven. Transportation and trade -- Part Eight. Tertiary economic activity -- Part Nine. Measurement, theory and planning.
Includes index.
Keywords: ECONOMIC